Daptomycin for Children in Clinical Practice Experience. Issue 6 (June 2016) - Garazzino, Silvia; Castagnola, Elio; Di Gangi, Maria; Ortolano, Rita; Krzysztofiak, Andrzej; Nocerino, Agostino; Esposito, Susanna; D'Argenio, Patrizia; Galli, Luisa; Losurdo, Giuseppe; Calitri, Carmelina; Tovo, Pier-Angelo
Abstract : Data on daptomycin use in the pediatric setting are scanty. We conducted a multicenter, retrospective study on 46 children treated with intravenous daptomycin at a mean dosage of 7.0 mg/kg/d, for a median of 14 days. Three children had adverse events possibly related to daptomycin. The drug was overall well tolerated, even with prolonged treatment.